Diagnostic predictive value of platelet indices for discriminating hypo productive versus immune thrombocytopenia purpura in patients attending a tertiary care teaching hospital in Addis Ababa, Ethiopia. Issue 1 (December 2016) - Negash, Mikias; Tsegaye, Aster; G/Medhin, Amha
Abstract Background Bone marrow examination may be required to discriminate causes of thrombocytopenia as hypoproductive or hyperdestructive. However, this procedure is invasive and time consuming. This study assessed the diagnostic value of Mean Platelet Volume (MPV), Platelet Distribution Width (PDW) and Platelet Large Cell-Ratio (P-LCR) in discriminating causes of thrombocytopenia as hypoproductive or hyperdestructive (Immune thrombocytopenia purpura). Method A prospective cross-sectional study was conducted on 83 thrombocytopenic patients (Plt < 150 × 109 /L). From these, 50 patients had hypoproductive and the rest 33 Immune Thrombocytopenia Purpura (ITP). Age and sex matched 42 healthy controls were included as a comparative group. Hematological analysis was carried out using Sysmex XT 2000i 5 part diff analyzer. SPSS Version16 was used for data analysis. A two by two table and receiver operating characteristic (ROC) curve was used to calculate sensitivity, specificity, positive and negative predictive values, for a given platelet indices (MPV, PDW and P-LCR). Studentt test and Mann WhitneyU test were used to compare means and medians, respectively. Correlation test was used to determine associations between continuous variables. Results All Platelet indices were significantly higher in ITP patients (n  = 33) than in hypoproductive thrombocytopenic patients (n  = 50) (p  < 0.0001). In particular MPV and P-LCR have larger area under ROC curve (0.876 and 0.816, respectively), indicating a better predictive capacity, sensitivity and specificity in discriminating the two causes of thrombocytopenia. The indices were still significantly higher in ITP patients compared to 42 healthy controls (p  < 0.0001). A significant negative correlation was observed between platelet count and platelet indices in ITP patients, (p  < 0.001). Conclusion MPV, PDW and P-LCR help in predicting thrombocytopenic patients as having ITP or hypoproductive thrombocytopenia. If these indices are used in line with other laboratory and clinical information, they may help in delaying/ avoiding unnecessary bone marrow aspiration in ITP patients or supplement a request for bone morrow aspiration or biopsy in hypoproductive thrombocytopenic patients.